Wound Healing - New Insights Into Ancient Challenges 2016
DOI: 10.5772/63566
|View full text |Cite
|
Sign up to set email alerts
|

Topical Wound Oxygen Versus Conventional Compression Dressings in the Management of Refractory Venous Ulcers

Abstract: Topical wound oxygen (TWO 2 ) proposes an innovative therapy option in the management of refractory non-healing venous ulcers (RVU) that aims to accelerate wound healing. TWO 2 accelerates epithelialisation. This leads to the development of a higher tensile strength collagen, which lessens scarring and the risk of recurrence. Sixty-seven limbs with 67 ulcers were managed using TWO 2 therapy, and 65 limbs with 65 ulcers were managed using conventional compression dressings (CCD). The proportion of ulcers comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…Due to the complex etiopathogenesis of such wounds, the most beneficial therapeutic results are obtained in case of multidirectional treatment model, taking into consideration the synergies between individual therapeutic methods, including also the physical ones. 23,24 The results of the current study have confirmed the therapeutic efficacy of both forms of T A B L E 1 Comparison of results concerning pain experienced, provided in Laitinen scale in both groups of patients undergoing treatment, before the beginning and after the completion of applied cycle of physical procedures (after 17 weeks), with statistical assessment as well as reduced pain intensity, whatever the ulceration etiology was. In some available papers the results of topical hyperbaric oxygen therapy were slightly better when compared to those obtained by application of only compression therapy and dressing.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Due to the complex etiopathogenesis of such wounds, the most beneficial therapeutic results are obtained in case of multidirectional treatment model, taking into consideration the synergies between individual therapeutic methods, including also the physical ones. 23,24 The results of the current study have confirmed the therapeutic efficacy of both forms of T A B L E 1 Comparison of results concerning pain experienced, provided in Laitinen scale in both groups of patients undergoing treatment, before the beginning and after the completion of applied cycle of physical procedures (after 17 weeks), with statistical assessment as well as reduced pain intensity, whatever the ulceration etiology was. In some available papers the results of topical hyperbaric oxygen therapy were slightly better when compared to those obtained by application of only compression therapy and dressing.…”
Section: Discussionsupporting
confidence: 73%
“…Treatment of wounds, particularly those which are hard to heal, should be conducted in a complex manner in specialized centers, as the therapeutic procedures provided at basic level are not sufficient in many cases, and do not give fully satisfactory results. Due to the complex etiopathogenesis of such wounds, the most beneficial therapeutic results are obtained in case of multidirectional treatment model, taking into consideration the synergies between individual therapeutic methods, including also the physical ones 23,24 . The results of the current study have confirmed the therapeutic efficacy of both forms of physical treatment compared, while the results in the group of patients where combined physical procedures were applied with the use of LASEROBARIA‐S device were significantly better.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…TOT is applied directly to the wound and does not require a full-body compression chamber. That is why TOT has much lower systemic complications and can be the alternative for patients with contraindication to HBOT [ 26 , 30 ].…”
Section: Oxygen Therapymentioning
confidence: 99%